MIMO Systems with Intentional Timing Offset. (15th March 2011) - (Nandan), Aniruddha Das; Rao, Bhaskar D.
Abstract : The performance of MIMO systems with intentional timing offset between the transmitters has recently been the focus of study of different researchers. In these schemes, a nonzero (but known) symbol timing offset is introduced between the signals transmitted from the different transmitters to improve the performance of MIMO systems. This leads to a reduction in Interantenna Interference (IAI), and it is shown that an advanced receiver can utilize this information to extract significant performance gains. In this paper, we show that this transmission scheme may be used in conjunction with different kinds of receivers including ZF, MMSE, and sequence detection-based receivers. We also consider the design of novel pulse shapes that reduce the IAI at the expense of slightly higher intersymbol interference (ISI) and show that additional gains may be achieved.